Несколько предельных теорем для процессов диффузионного типа в Rm - Писанец, С.И. (Український математичний журнал, 1993)
For a sequence of stochastic equations of diffusion type, the conditions, which arc close to necessary and sufficient ones, are found for the weak convergence of measures μ(ξ(n),w),n=1,..., which correspond to solutions, to the limit measure μ(ξ(0),w). The conditions are also found under which the weak convergence of solutions of stochastic equations implies the strong convergence.